PREVALENCE OF HEPATITIS C VIRUS ANTIBODIES IN RENAL TRANSPLANTED PATIENTS AND ITS IMPORTANCE - M.T. AKPOLAT; T. ARINSOY; N. ARIK; C. ÖZKUYUMCU; H. ŞİMŞEK and C. SUNGUR and Ü. YASAVUL and Ç. TURGAN and Ş. ÇAĞLAR and H. TELATAR (Turkish Journal of Gastroenterology, 2020)
-